Institutions, Events and Theory: A Comparison of the Monetary Policy Reforms of 1844/45 in England and Sweden. - Lobell, Håkan (Social Science Spectrum, 2018)
The paper analyses the role of ideas, past experience and crises in the process leading to theoretical and political disputes and the changes of monetary and banking policy in Sweden in 1844/45. It also analyses the role of institutional settings and types of actors involved in the decision-making process. A comparative approach is deployed. Policy changes at the time in the poor and peripheral Sweden is contrasted with the well-known developments in England. The results suggest that current events and past experience were important factors. Purely theoretical considerations played a somewhat lesser role in determining the policy-change. Institutional peculiarities and country characteristics did not significantly alter the core outcomes, but certain specific features. Probably an influx of ideas, policies and experiences from England also influenced policy choices in the case of Sweden.